Characterization of Knee Meniscal Pathology: Correlation of Gross, Histologic, Biochemical, Molecular, and Radiographic Measures of Disease - Roller, Brandon L.; Monibi, Farrah A.; Stoker, Aaron M.; Kuroki, Keiichi; Bal, B. Sonny; Cook, James L. (The Journal of Knee Surgery, 2015)
Meniscal pathology is an extremely prevalent problem, which inevitably leads to osteoarthritis and associated pain, swelling, and disability. Relatively little data are available regarding the molecular, biochemical, and histologic aspects of meniscal disease. This study characterizes meniscal pathology in the presence of symptomatic osteoarthritis and correlates clinical and basic science data in an attempt to delineate clinically relevant mechanisms of disease. Twenty-seven knees from 23 patients who underwent total knee arthroplasty comprised the affected group and 6 aged nonsymptomatic knees were used as controls. All meniscal tissues were harvested and subjectively scored for gross and histologic pathology. Biochemical analyses were performed to determine glycosaminoglycan (GAG) content, collagen (hydroxyproline) content, and water content. Real-time polymerase chain reaction analysis was conducted for genes involved in synthesis (collagens [col] 1, 2, 3, and 6), degradation (matrix metalloproteinases [MMP-1, -2, -3, -13]), and angiogenesis (vascular endothelial growth factor). Weight-bearing, anterior-posterior radiographic views were used to determine joint space measurements for lateral and medial compartments, and were subjectively scored for osteoarthritic changes. Data were compared for statistically significant differences and to determine the presence and strength of correlations among variables assessed. Affected menisci had significantly higher gross and histologic pathology scores compared with control menisci. Affected menisci had significantly higher water, proteoglycan, and collagen content compared with control menisci. Col 1, 3, and 6 gene expression levels for the affected group were significantly increased compared with controls. MMP-13 expression was significantly increased for the affected group. MMP-2 and -3 expression levels were significantly lower in the affected group compared with controls. The affected group had significantly more joint space narrowing and higher radiographic scores for medial compared with lateral compartments. Several strong and moderately strong correlations were present between variables. These data suggest that in vitro measures of meniscal pathology have potential value for understanding disease mechanisms and predicting clinical disease.
Keywords: meniscus; pathology; osteoarthritis; knee